REGULATORY INFORMATION MANAGEMENT: Novel Approaches for Health Care System - Saha, D. (BALI MEDICAL JOURNAL, 2013)
In managing chemistry, manufacturing and controls documents; the larger process is involved for electronic regulatory submissions to health authorities. This is a case of an entire process standard providing significant gains in efficiency. A solution is needed for this area of the biopharmaceutical industry. Within a Regulatory affiars, there are Information Management needs, particularly related to the electronic Common Technical Document (eCTD) submission process. There are a number of methods for adding efficiencies to the submission process, particularly through automation and standards. Consider the overall process of a sponsor producing an eCTD submission and within it the specific process of transferring Chemistry, Manufacturing and Controls (CMC) documents from a manufacturer to the sponsor. Keeping in mind the overall eCTD process, consider the specific CMC process to illustrate where and how inefficiencies can be changed.